Evaluation of cross‐neutralizing immunity following COVID‐19 primary series vaccination during the Omicron surge in Tanzania - Nkinda, Lilian; Barabona, Godfrey; Ngare, Isaac; Nkuwi, Emmanuel; Kamori, Doreen; Msafiri, Frank; Kunambi, Ponsian P.; Osati, Elisha; Kidenya, Benson R.; Chuwa, Harrison; Kinasa, Glory; Hassan, Frank E.; et al. (Journal of Medical Virology, 2024)
COVID‐19 vaccine became available in Tanzania during the first wave of the Omicron variant. During that time community seroprevalence of SARS‐CoV‐2 was already at 50%–80%. To date, it remains largely unknown whether ongoing vaccination with the primary series vaccines has any meaningful immune‐boosting effects against newer Omicron subvariants. Therefore, we tested cross‐neutralizing capacity of antibodies elicited by infection, vaccination, or both against SARS‐CoV‐2 Omicron subvariants BA.1, and the newer subvariants BQ.1.1 and XBB.1.5. that were unexperienced by this population. Participants who were either SARS‐CoV‐2 infected‐only (n = 28), infected vaccinated (n = 22), or vaccinated‐only (n = 73) were recruited from Dar‐es‐Salaam, Tanzania, between April and December 2022. Plasma 50% neutralization titers (NT50) against SARS‐CoV‐2 wild‐type strain and Omicron subvariants were quantified by a lentiviral‐based pseudo‐virus assay. Percentage of participants with neutralizing activity against WT and BA.1 was high (>85%) but was reduced against BQ.1.1 (64%–77%) and XBB.1.5 (35%–68%) subvariants. The low median cross‐neutralization titer was slightly higher in the infected vaccinated group compared to vaccine‐only group against BQ.1.1 (NT50 148 vs. 85, p = 0.032) and XBB.1.5 (NT50 85 vs. 37 p = 0.022) subvariants. In contrast, vaccine‐boost among the infected vaccinated did not result to increased cross‐neutralization compared to infected‐only participants (BQ.1.1 [NT50 of 148 vs. 100, p = 0.501] and XBB.1.5 [NT50 86 vs. 45, p = 0.474]). We report severely attenuated neutralization titers against BQ.1.1 and XBB.1.5 subvariants among vaccinated participants, which marginally improved in the infected vaccinated participants. Our findings call for further studies to evaluate effectiveness of the primary series vaccines in preventing severe infection and mortality against the newer variants.